2021
DOI: 10.3390/su13147806
|View full text |Cite
|
Sign up to set email alerts
|

Differences on Habitual Physical Activity Index in Primary Schoolchildren according to Age and Gender

Abstract: The World Health Organization (WHO) has warned that a large majority of children do not reach its recommendations on physical activity for health, i.e., 60 min a day of moderate to vigorous physical activity. The objective of this study was to know the index of habitual physical activity in different contexts where the child interacts: school index (SCHOOL-I), extracurricular/sports activity index (SPORT-I), free time index (LEISURE-I) and the total habitual physical activity index (GLOBAL-I) based on age and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Although children's postural control depends on the interactions between sensory information and motor performance, it is also conditioned by the maturation of the structures involved and acquisitions related to motor experiences [25]. Indeed, it has been reported that young children can use sensory information and modify motor behaviour in response to the challenges of the environment, learning through experiences [16], and that physical activity programmes must be carried out from early childhood in children aged 3 to 6 years old, and not wait until primary education, to establish sustainable healthy lifestyle habits [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although children's postural control depends on the interactions between sensory information and motor performance, it is also conditioned by the maturation of the structures involved and acquisitions related to motor experiences [25]. Indeed, it has been reported that young children can use sensory information and modify motor behaviour in response to the challenges of the environment, learning through experiences [16], and that physical activity programmes must be carried out from early childhood in children aged 3 to 6 years old, and not wait until primary education, to establish sustainable healthy lifestyle habits [38].…”
Section: Discussionmentioning
confidence: 99%
“…According to new guidelines released by the World Health Organization (WHO), "regular physical activity may contribute to addressing the global learning crisis, as it is associated with better brain health, which includes cognitive development, classroom behaviour (e.g., time spent on tasks) and academic performance" [37]. Indeed, it has been suggested that solid physical activity promotion programmes are needed to promote the practice, both within the school environment and after school, considering families as potential influencers on children's lifestyles [38]. Promoting postural health in children, focused on developing capacities related to improvements in knowledge, competencies and commitment of all community members [29], benefits children's individual well-being, and can positively impact environmental and social sustainability by promoting healthy and conscious lifestyles.…”
Section: Introductionmentioning
confidence: 99%
“…Spanish primary school children (n = 900, aged 10–12 years) engaged in higher levels of PA during school when compared to the PA they engaged in during sport and leisure-time activities [ 16 ]. Burns et al [ 17 ] meta-analysed studies (n = 10) that met the eligibility criteria of their research in the pursuit of determining the impact school-based PA initiatives had on children’s (n = 2617, aged 6.04–15.04 years) enjoyment levels when participating in PA.…”
Section: Introductionmentioning
confidence: 99%
“…SP is a subset of PA and youth sport has been defined as a program that provides a systematic sequence of practices and contests for children and youth [ 26 ]. Many studies show that SGC activities are effective in improving children’s FV intake nowadays [ 27 , 28 , 29 ], and that different forms of SP can have a significant effect on improving children’s MVPA (especially sports that are both fun and challenging to ensure adherence to the intervention) [ 30 , 31 , 32 , 33 ]. However, research in this area is still very limited in China.…”
Section: Introductionmentioning
confidence: 99%